Electronic patient agenda forms: comparing agreement between the reason for specialty consultation reported by referring providers and patients. (2nd January 2019) - Ahmed, Shahzad; Almario, Christopher V.; Chey, William D.; Robbins, Lori A.; Chang, Bianca; Ahn, Joseph; Ko, Jeffrey; Gu, Phillip; Siu, Alvin; Spiegel, Brennan M.R.
ABSTRACT: Objective : Little is known about the agreement between referring providers' reason for specialty evaluation and patients' understanding of why they are referred for consultation. Here, we compared the reason for consult (RFC) documented by referring providers during usual care vs. the perceived RFC independently reported by patients through an e-portal just prior to the specialist visit. Methods : We performed an observational study among patients referred for gastrointestinal (GI) evaluation. Patients referred to the specialty clinic submitted their self-reported RFC using an online patient agenda form prior to their visit. Therefore, each participant had a referring provider- and patient-documented RFC. Blinded physicians reviewed the RFCs in random order using a priori coding criteria. We then compared whether the provider and patient RFC pairs were concordant (i.e., ≥1 clinical topic[s] in the RFCs matched). Results : Sixty patients completed the e-portal prior to their visit, leading to 60 provider-patient RFC pairs. The RFC pairs were concordant in only 52% of cases. Conclusions : There is poor agreement between referring providers' reason for GI referral and patients' understanding of why they are visiting the clinic. Future research examining whether electronic patient agenda forms impact diagnostic and management precision, patient satisfaction, and healthcare utilization is warranted.